Persistence of Real Exchange Rates in the Central and Eastern European Countries - Baharumshah A.Z.; Soon S.-V.; Fountas S.; Mohamad Shariff N.S. (Taylor and Francis Inc., 2024)
Indexed by WOS/ Scopus